Optimization of Refining and Deodorization Process of Beef Flank Fat and Analysis of Volatile Components - Wang, Yushu; Bai, Jiaxuan; Chu, Chunxia; Li, Zien; Gong, Yihan; Li, Wenjing; Xing, Yanxia (International Journal of Agriculture and Food Sciences Research, 2025)
To address the issues of missing processing standards for beef kidney fat and unstable flavor quality, this study aims to optimize refining and deodorizing process parameters and investigate their impact on volatile components to improve beef fat quality. In the refining process of beef kidney fat, three factors—refining temperature, refining time, and refining speed—were studied for their effects on sensory quality. Single-factor experiments and orthogonal experiments determined the optimal combination as a refining temperature of 150°C, refining time of 90 minutes, and refining speed of 600 rpm. In the deodorizing process, single-factor experiments and orthogonal experiments were used to determine the effects of deodorizing temperature, deodorizing speed, and deodorizing time on the iodine value of beef kidney fat, with the best combination being a deodorizing temperature of 55°C, deodorizing time of 30 minutes, and deodorizing speed of 70 rpm. Additionally, to further explore the impact of vacuum deodorization on the volatile components of beef kidney fat, purge-and-trap gas chromatography-mass spectrometry (P&T-GC-MS) was used for qualitative analysis of the volatile components in refined and deodorized beef kidney fat. Partial least squares discriminant analysis (PLS-DA) based on absolute content was employed to comprehensively evaluate flavor changes. The results showed that the optimized vacuum deodorization process systematically improved the flavor quality of beef kidney fat by enriching flavor substances and removing impurities, providing a theoretical basis for standardized industrial production.